Analysis Of Basic Technical Skills For Playing Soccer In Batu City Ssb Blue Eagle Players - Pratama, Rovino Chandra; Kusmawati, Wiwik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the basic technical skills of playing soccer in SSB Blue Eagle players in Batu City. The subjects of this research were 65 Batu City SSB Blue Eagle players. This research is quantitative descriptive research, the research method is a survey method with data collection techniques using tests and measurements. The data obtained is in the form of test results and measurements of the skills of Batu City SSB Blue Eagle players. on the basic techniques of the game of football. skill level It can be concluded that the basic techniques for playing football in Batu City SSB Blue Eagle participants are in the very good category as many as 7 students or 10.76%, 18 students or 27.69% in the good category, 32 students in the fair category or 27.69%. 49.24% and in the less than category there were 4 students or 6.15% and in the very less category there were 4 students or 6.15%.